The potential role of methyltransferase-like 5 in deficient mismatch repair of uterine corpus endometrial carcinoma. Issue 3 (1st March 2022) - Liu, Xiaojuan; Ma, Hui; Ma, Lisha; Li, Kun; Kang, Yanhua
ABSTRACT: To explore the potential function of methyltransferase-like 5 (METTL5) in uterine corpus endometrial carcinoma (UCEC) and verify the relationship between deficient DNA mismatch repair (MMR) and METTL5. We used bioinformatics to predict the possible role of METTL5 and molecular biology methods to analyze METTL5 expression. We observed UCEC proliferation, development, and apoptosis using a METTL5 knockdown lentivirus and, coupled with METTL5 bioinformatics and Western blot analysis, detected microsatellite instability (MSI) and MMR. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed. Finally, some METTL5-associated gene mutations in UCECs were detected. Results show that METTL5 expression in UCEC tumor tissue was increased, and UCEC patients with high METTL5 expression had worse prognostic outcomes. We also observed the highest METTL5 expression level in KLE cells. Furthermore, knocking down METTL5 weakened the proliferation, reduced tumor volume and biomarkers, and increased apoptosis. Moreover, METTL5 knockdown induced the MSH2, MSH6 and PMS2 expression in MMR. METTL5 was negatively correlated with gene silencing, mRNA binding, olfactory receptor activity, antigen processing and presentation, cytosolic DNA sensing, olfactory transduction, and RIG-1-like and Toll-like receptor signaling pathways. METTL5 may regulate MMR protein levels in UCECs, thus enhancing UCEC proliferation, development, and prognosis. Graphical Abstract: uf0001